Uric acid and metabolic syndrome: Findings from national health and nutrition examination survey - Bowden, Rodney G.; Richardson, Kathleen A.; Richardson, Luke T. (Frontiers in Medicine, 2022)
Introduction: Hyperuricemia commonly associated with Gout has been proposed as an independent risk factor for Metabolic Syndrome. Objective: The purpose of the study was to determine if there is a relationship between hyperuricemia and Metabolic Syndrome. Methods: An analysis of cross-sectional data was conducted using the 2013-2018 NHANES datasets. Sample weights were assigned by NHANES researchers to each participant allowing researchers to generalize results to all non-institutionalized US civilians. The analysis included 6,432 individuals, which were representative of 94,729,059 US citizens. Results: Pearson’s correlations, chi-square tests, and logistic regression equations were calculated to determine the association between hyperuricemia and metabolic syndrome. In an unadjusted regression analysis, individuals with hyperuricemia (above 7.0 mg/dL in males and 6.0 mg/dL in females) were 3.19 times more likely to have Metabolic Syndrome compared to those with normal uric acid levels. When controlling for various confounding variables those with hyperuricemia were 1.89 and 1.34 times more likely to have Metabolic Syndrome than those with normal uric acid levels in two additional logistic regression models. Conclusions: In this large cross-sectional study, hyperuricemia was found to be associated with Metabolic Syndrome. Additional analyses that controlled for various risk factors previously identified as predictive of Metabolic Syndrome still demonstrated hyperuricemia independently associated with Metabolic Syndrome. The results of this study suggest a need to understand the metabolic pathways of uric acid more clearly to further explain the contribution to Metabolic Syndrome. Additional research should include prospective clinical trials assessing the effects of uric acid and the control of uric acid on Metabolic Syndrome and concomitant medical outcomes.